Fluorine-containing aryloxyethyl thiocyanate derivatives are potent inhibitors of Trypanosoma cruzi and Toxoplasma gondii proliferation - Garcia Liñares, Guadalupe Eugenia (2007)
As a part of our project aimed at developing new safe chemotherapeutic and chemoprophylactic agents against tropical diseases, fluorine-containing drugs structurally related to 4-phenoxyphenoxyethyl thiocyanate (1) were designed, synthesized, and evaluated as antiproliferative agents against Trypanosoma cruzi, the parasite responsible of American trypanosomiasis (Chagas' disease), and Toxoplasma gondii, the etiological agent of toxoplasmosis. This thiocyanate derivative had previously proven to be an effective agent against T. cruzi proliferation. Fluorine-containing thiocyanate derivatives 2 and 3 were threefold more potent than our lead drug 1 against intracellular T. cruzi. The biological evaluation against T. gondii was also very promising. The IC50 values corresponding to 2 and 3 were at the very low micromolar level against tachyzoites of T. gondii. Both of these drugs are interesting examples of effective antiparasitic agents that have outstanding potential not only as lead drugs but also to be used for further in vivo studies.